Piggybacking strategies for nonprofits: A shared costs approach - Nielsen, Richard P. (Strategic Management Journal, 1986)
Abstract This article presents case data and a conceptual foundation for nonprofit piggybacking whereby a nonprofit organization subsidizes its deficit producing primary mission by diversifying into related surplus‐producing ventures. Shared common and joint costs are considered as supply‐side bases for selecting among demand‐side related diversification activities.